Musicians in the making: pathways to creative performance - Rink, John; Gaunt, Helena; Williamon, Aaron (New York Oxford university press, 2017)
Musicians are continually 'in the making', tapping into their own creative resources while deriving inspiration from teachers, friends, family members and listeners. Amateur and professional performers alike tend not to follow fixed routes in developing a creative voice: instead, their artistic journeys are personal, often without foreseeable goals. The imperative to assess and reassess one's musical knowledge, understanding and aspirations is nevertheless a central feature of life as a performer.Musicians in the Making explores the creative development of musicians in both formal and informal learning contexts. It promotes a novel view of creativity, emphasizing its location within creative processes rather than understanding it as an innate quality. It argues that such processes may be learned and refined, and furthermore that collaboration and interaction within group contexts carry significant potential to inform and catalyze creative experiences and outcomes. The book also traces and models the ways in which creative processes evolve over time.Performers, music teachers and researchers will find the rich body of material assembled here engaging and enlightening. The book's three parts focus in turn on 'Creative learning in context', 'Creative processes' and 'Creative dialogue and reflection'. In addition to sixteen extended chapters written by leading experts in the field, the volume includes ten 'Insights' by internationally prominent performers, performance teachers and others. Practical aids include abstracts and lists of keywords at the start of each chapter, which provide useful overviews and guidance on content.Topics addressed by individual authors include intrapersonal and interpersonal dynamics, performance experience, practice and rehearsal, 'self-regulated performing', improvisation, self-reflection, expression, interactions between performers and audiences, assessment, and the role of academic study in performers' development.